Improving the Health Level of the Young Generation: Implementation of School Health Efforts at Inpres Doyo Baru and Besum State Elementary Schools, Jayapura Regency - Karim, Muammar; Wahyuti, Wahyuti; Anggai, Martapina; Makaba, Sarce; Hasmi, Hasmi; Medyati, Novita; Tingginehe, Rosmin Mariati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the efforts of two elementary schools, namely Inpres Doyo Baru and Besum State Elementary Schools in Jayapura Regency, in implementing School Health Efforts. This research uses a qualitative descriptive method with a case study approach. Data collection was carried out through in-depth interviews with 12 informants, consisting of 10 key informants, 6 main informants, and 3 additional informants. The results of this study reveal that both schools integrate health education in the curriculum, especially in subjects sports physical Education and health and Scouts. A school environment that is free from bullying and violence, as well as the availability of clean and well-maintained toilets, also supports the creation of a healthy learning environment. Support from School Operational Assistance funds and active participation from various parties, including the government, non-government organizations and the community, are important factors in the smooth running of the School Health Business program. The efforts of the Inpres Doyo Baru and Besum State Elementary Schools in implementing School Health Efforts show their commitment to building a healthy and quality young generation.